2007
DOI: 10.1002/art.22417
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of matrix metalloproteinase gene expression by a retinoid X receptor–specific ligand

Abstract: Objective. To evaluate the effects of LG100268 (LG268), a synthetic ligand for the nuclear hormone receptor retinoid X receptor, on the expression of matrix metalloproteinase 1 (MMP-1) and MMP-13 induced by proinflammatory cytokines in a chondrocyte model.Methods. SW-1353 human chondrosarcoma cells were used to study the effects of LG268 on interleukin-1␤ (IL-1␤)-stimulated MMP production and collagen degradation. Gene expression was determined by quantitative real-time reverse transcriptionpolymerase chain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 46 publications
4
45
0
Order By: Relevance
“…For instance, interleukin-1β, UV radiations or phorbol esters, increase proMMP-1 gene expression through histone posttranslational modifications (22,29). In this study we observed that accumulation of hyperacetylated histones is not a sufficient trigger to enhance either proMMP-1 gene expression or chromatin global decondensation in HT1080 fibrosarcoma cells.…”
Section: Discussionmentioning
confidence: 60%
“…For instance, interleukin-1β, UV radiations or phorbol esters, increase proMMP-1 gene expression through histone posttranslational modifications (22,29). In this study we observed that accumulation of hyperacetylated histones is not a sufficient trigger to enhance either proMMP-1 gene expression or chromatin global decondensation in HT1080 fibrosarcoma cells.…”
Section: Discussionmentioning
confidence: 60%
“…Treatment of primary chondrocytes and cell lines with IL-1␤ dramatically increases transcription of MMP-13, with a concordant increase in collagen destruction (6 -8). AP-1 response elements have been identified in the proximal promoter region of MMP-13, through sequence analysis and by reporter assays utilizing both stably and transiently transfected reporter constructs (5,9,10). A puzzling aspect of these studies, however, is that reporter constructs driven by the MMP-13 proximal promoter often do not mimic the expression pattern of endogenous MMP-13 (5, 9, 11).…”
Section: Matrix Metalloproteinases (Mmps)mentioning
confidence: 99%
“…In another study, Elliot's group also showed that synthetic triterpenoid, CDDO, inhibited IL-1 induced MMP-1 and MMP-13 expression in SW-1353 cells (Elliott et al, 2003). While Burrage et al evaluated the effect of synthetic ligand LG 100268 for nuclear hormone receptor and it selectively inhibit IL-1 and stimulate MMP-1 and MMP-13 (Burrage et al, 2007).…”
Section: Discussionmentioning
confidence: 99%